Drugs targeting the bone microenvironment: new therapeutic tools in Ewing's sarcoma?. (September 2013) - Redini, Francoise; Odri, Guillaume A; Picarda, Gaëlle; Gaspar, Nathalie; Heymann, Marie-Françoise; Corradini, Nadege; Heymann, Dominique
Abstract : Introduction: Ewing's sarcoma (ES) is the second most frequent malignant primary bone tumour in children, adolescents and young adults. The overall survival is 60 – 70% at 5 years but still very poor for patients with metastases, disease relapse or for those not responding to chemotherapy. For these high risk patients, new therapeutic approaches are needed beyond conventional therapies (chemotherapy, surgery and radiation) such as targeted therapies. Areas covered: Transcriptomic and genomic analyses in ES have revealed alterations in genes that control signalling pathways involved in many other cancer types. To set up more specific approaches, it is reasonable to think that the particular microenvironment of these bone tumours is essential for their initiation and progression, including in ES. To support this hypothesis, preclinical studies using drugs targeting bone cells (bisphosphonate zoledronate, anti-receptor activator of NF-κB ligand strategies) showed promising results in animal models. This review will discuss the new targeted therapeutic options in ES, focusing more particularly on the ones modulating the bone microenvironment. Expert opinion: Targeting the microenvironment represents a new option for patients with ES. The proof-of-concept has been demonstrated in preclinical studies using relevant animal models, especially for zoledronate, which induced a strong inhibition of tumour progression in an orthotopic bone model.